Digital transformation of planning in the pharmaceutical sector - Ingrid Yohana Carrillo Barreto; Ana María Jiménez Tocasuche; Angie Jimena Colorado Gonzalez; María Fernanda Durán Sanjuán; Andrés Felipe Santos Hernández (Changing Tides: The New Role of Resilience and Sustainability in Logistics and Supply Chain Management – Innovative Approaches for the Shift to a New Era. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 33, 2022)
Purpose: To adjust the inventory supply planning, through digital transformation that allows automation and tracking of demand behavior in real time and with low cost tool. Methodology: The collected database is loaded into an Excel along with the required input variables in each of the inventory policies. The data is processed and imported into Python, the demand forecasting is made and the policies are simulated to choose the one that generates the lowest cost. Results: The algorithm indicates the inventory scheduling to be implemented by the company according to the policy that allows the lowest costs and that supplies the demand of each product. Originality: The design of an original tool, that allows obtaining accuracy of the inventory management, with easy interaction of the user and the algorithm, through the reception of information and output of results in Excel, processed by python, across the synergy between the two programs.
urn:nbn:de:gbv:830-882.0200595; hdl:10419/267179; https://econpapers.repec.org/RePEc:zbw:hiclpr:33
Keywords: 650; Innovation Management; Technology Management